ANALISIS PERBANDINGAN KINERJA KEUANGAN PERUSAHAAN INDEKS LQ-45 DENGAN PERUSAHAAN INDEKS HIGH DIVIDEND 20 DALAM PENENTUAN KEBIJAKAN DIVIDEN PADA SEKTOR INFRASTRUKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA. - Rambi, Riena Millenia Mahdalena; Tinangon, Jantje J.; Datu, Christian (GOING CONCERN : JURNAL RISET AKUNTANSI, 2021)
Financial performance is one of the company’s considerations in determining dividend policy, affected by the opinions and assessments of investors as an external funding source. The purpose of this study is to determine the difference in financial performance using financial ratios, between LQ-45 index and High Dividend 20 index of the Infrastructure sector. This study uses a comparative quantitative approach. The analytical technique used in this study is two-average difference test (independent sample t-test). Based on criteria, there are 7 infrastructure sector companies listed in LQ-45 index and High Dividend 20 index. The results of the study prove that there are significant differences in financial ratios of DER, ROA, NPM, and DPR, while for CR and TATO ratios it is found that there is no significant difference between the two indices in 2017-2019. The analysis conducted shows that the infrastructure sector listed in High Dividend 20 index have better financial performance seen from DER, TATO, ROA, NPM, and DPR ratio, and infrastructure sector companies listed in LQ-45 index have a good performance in terms of CR ratios.